Rapid Multi-Residue Method for Simultaneous Determination of 1,3,5-Triazine Herbicides in Environmental Samples by Capillary GC-MS-EI Selective Ion Monitoring Method - Perumal E. Ravi; Perumal E. Thirugnanam; Jothi Ramalingam Rajabathar; Hamad Al-Lohedan; S. Jenifer; Muthusamy Karnan (Separations, 2023)
A new multi-residue method using gas chromatography–mass spectrometry electron ionization selective ion monitoring mode (SIM) has been developed for the simultaneous determination of eight 1,3,5-triazine herbicides such as 1,3,5-triazine-2,4-diamine (atrazine), ametryn, prometryn, propazine, terbuthylazine, terbutryn, and simazine simetryn in water and soil samples. Quantification is done using lindane (gamma benzene hexachloride) as an internal standard. A specific Capillary DB-Wax column of 30 m length, 0.32 mm internal diameter, and 0.25 µm film thickness is used for the separation of eight 1,3,5-triazine-2,4-diamine. The method was applied for the determination of residues in groundwater and soil samples. The lowest detection limit by GC-MS-SIM (selective ion monitoring mode) is 0.1 pg/mL. Recovery in water samples is in the range of 93–103%, and in soil samples, 91–102% for different individual compounds. Forty-five groundwater and soil samples were collected in and around Kancheepuram district in Tamilnadu (India), and they were analyzed for the respective residues. A detailed discussion of the GC-MS analysis results has been presented.